Novel Hydrothermal Synthesis of Flower Like ZnO Nanostructures and Investigation of their Gas – Sensing Properties - Siril, V. S.; Madhusoodanan, K. N. (Recent Progress in Science and Technology Vol. 5, 2023)
Flower like nanostructures of ZnO have been successfully fabricated by a novel hydrothermal technique. Various sample characterization methods, including XRD, FESEM, SEM, TEM, have been employed. The synthesised ZnO samples exhibited a well defined crystal structure of hexagonal phase. The average crystallite size for ZnO sensors was estimated to be 31 nm. The flower shaped nanorods were \(\sim\)84 nm in diameter and \(\sim\) 1 µm in length. The response to the reducing gas NH3 was evaluated in terms of the operating temperature, sensitivity, response time/ recovery time of the ZnO-based gas sensor. At a working temperature of \(230^{°}\)C, the lowest detection limit for ammonia gas was found to be 5 ppm.